Phytochemical Profile of Pasture Weeds from the Brazilian Cerrado - RODRIGUES,D.A. (2019)
ABSTRACT: The great diversity of plant species in pastures of the Brazilian Cerrado with distinct ecophysiological characteristics indicates the possibility of finding, in the cellular content of this flora, chemical compounds with potential for use in agriculture and human and animal health. Three steps are necessary to prove this hypothesis: phytochemical prospecting, characterization of secondary metabolites, and studies on the biological activities of these metabolites present in these plants. The chemical profile of secondary metabolites present in five species of the Brazilian Cerrado (Davilla elliptica, Remijia ferruginea, Luehea paniculata, Anacardium occidentale, and Acosmium dasycarpum) was traced in this research. These plant species were collected in pasture areas of Felício dos Santos, Minas Gerais. The samples were dried and submitted to two types of extract (ethanolic and hexanic). By using specific chemical reactions, the presence of coumarins, triterpenes/steroids, and anthracenosides was observed in the hexanic extracts, while the presence of alkaloids, triterpenes/steroids, flavonoids, tannins, reducing compounds, and anthocyanins was observed in the ethanolic extracts. The species presented diverse classes of compounds. However, triterpenes/steroids, tannins, reducing compounds and anthocyanins were found in all species, being the use of the solvent ethanol the most efficient in extracting the compounds. The species D. elliptica presented the highest number of classes of compounds. The widespread application in folk medicine justifies further studies on the biological activity of different metabolites in agriculture and health areas.